“Awig-Awig As Traditional Law Written in Traditional Law Perspective in Indonesia” - Wiwin Yulianingsih; Yana Indawati; Adhitya Widya Kartika (Nusantara Science and Technology Proceedings, 2020)
This study aims to find that customary law regulations exist in written form. This research also wants to prove that the customs regulations in each region in Bali are different according to the customs of other regions in Indonesia and the existence of this awig-awig still exists according to the needs of the community according to current conditions. Awig- awig is a system of social life that is characterized by several characteristics, such as interaction, binding patterns of unique behavior in all aspects of life that are steady and continuous, as well as a sense of identity towards the group in which the individual is a member. Awig-awig is made as an effort to maintain order and peace between indigenous villagers. The method used in this study begins with identification from various literature related to customary law in Indonesia. Then arranged in such a way as to bring up the right problem formulation which later can be comprehensively reviewed through field studies, literature studies, and direct observation, especially related to the problems taken in this research, namely awig-awig as customary law written in the perspective of Indonesian customary law. The results of the research in this study are expected to be able to contribute positively to the development of Customary Law Courses.